Assessment of mean respiratory rate from ECG recordings for risk stratification after myocardial infarction - Sinnecker, Daniel; Dommasch, Michael; Barthel, Petra; Mueller, Alexander; Dirschinger, Ralf J.; Hapfelmeier, Alexander; Huster, Katharina M.; Laugwitz, Karl-Ludwig; Malik, Marek; Schmidt, Georg (Journal of Electrocardiology, 2014)
Background We recently reported that nocturnal respiratory rate (NRR) predicts non-sudden cardiac death in survivors of myocardial infarction (MI). Here, we present the details of the technique deriving NRR from ECG recordings. Methods Continuous ECG and respiratory chest excursions were simultaneously recorded in 941 MI survivors who were followed-up for 5-years. Mean respiratory rate was derived from the ECG based on RR intervals, QRS amplitudes, and QRS vectors and compared to chest belt measurements. NRR was calculated from Holter-ECGs accordingly using the same ECG processing. Results Directly-measured and ECG-derived respiratory rates were in good agreement. Areas under the ROC curve for 10-min-ECG- and Holter-derived respiratory rate were well in the confidence intervals of that of the chest belt measurement. The optimum dichotomy of NRR for the prediction of mortality was ≥ 18.6 breaths per minute. Conclusions The mean respiratory rate can be precisely derived from continuous ECGs. © 2014 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: ECG; Myocardial infarction; Nocturnal respiratory rate